A decentralized autonomous personal data management system in banking sector - Gustina Zainal, M. Anna (2022)
The present security systems encounter vulnerable surveillance and protection breaches in financial domains day by day. These systems compromise the privacy of the users in such a way that their personal data are collected and controlled by the third-parties. In this regard, Bitcoin has been implemented in the financial space. It has made possible the trusted and auditable computing via decentralized network associated with a public ledger. This work proposes a decentralized personal data management system for banking sector using block chain which makes sure that the user can control their personal data in their own .It presents a Privacy-Protected Blockchain network in which all data is encoded within a controlled time period. Despite the fact that the data is available in the past, this design can successfully preserve user privacy and protect from deceivers, providing the data more stable and healthier. Blockchain has its advantages over features such as transparency, decentralization and immutability. In the proposed model, a protocol is implemented which converts the blockchain into automated access control manager. There is no need for a third party to be trusted for the implementation of this model. In the proposed system, the transactions are not limited to financial transactions like Bitcoin, it also includes data storing, sharing and querying. Hence, the use of blockchain could reduce the overly concern about securing and compartmentalizing the data.